(Design of Cocoa Butter and Cocoa Powder Equipments for Small Scale Industry) - Agus Sudibyo; Aan Yulistia; Dheni Mita Mala (Warta Industri Hasil Pertanian, 2005)
Research on design of cocoa better and cocoa powder equipments for small scale industry was conducted.The steps of this experimental were a literature study,comparative study and plant visit on the large cocoa and chokolate industries,design equipment to produce cocoa butter and cocoa powder for small scale industry,peformance test of equipments and analysis of cocoa butter and coco powder products using Indonesia National Standard (SNI)requirements.The treatment conducted consist of the effect of temperature extraction in hydrolic pressing and the effect of alkalization with sodium hydroxide and sodium carbonate in 4% concentration.The result showeds that the a set of cocoa butter and cocoa powder processing equipment were able to be implemented for small industry by small modification.The performance of the equipment in term of efficiency on cacao bean peeling,throw put capacity of peeling, roasting energy consumption,efficiency of cocoa paste grinding and efficiency of hydrolicpressing were 81,29%,34.kgs per hour,4.92 liters of kerosene per 20 kgs of cocoa bean 83,5% and 28,7% respectively. The cocoa bitter and cocoa powder product have not fulfilled the requirements of Indonesia National Standard(SNI) in term of fat content of cocoa butter;water content,fat content,ash content and vthe degree of particle size loose in mesh number 200 of cocoa powder.